Microstructural and Thermal Investigations of Cu-Al-Mn-Ni Shape Memory Alloys - Aksu Canbay, Canan; Sampath, V. (Elsevier Science Bv, 2017)
Shape memory alloys manifest two distinct characteristics, namely shape memory effect and superelastic effect. They are used in a wide variety of engineering, medical and commercial applications. The use of shape memory alloys in a particular application depends on the shape memory characteristics, viz., shape recovery strain and transformation temperatures. The martensitic transformation and its reversibility form the basis of these functional properties. The transformation temperatures are much influenced by alloying addition, grain-refinement, thermomechanical treatment, etc. In this work, the effect of composition, in general, and that of nickel, in particular, on the microstructure and transformation temperatures and thermodynamic parameters have been explored. The microstructural and phase analyses were carried out by optical microscopy and X-ray diffraction, respectively. The thermodynamic quantities/parameters, such as enthalpy and entropy associated with the transformations as well as the transformation temperatures, were determined by differential scanning calorimetry. The phase analyses were also carried out by thermogravimetry and differential thermal analysis. The results have been analysed and discussed in this paper. (C) 2017 Elsevier Ltd. All rights reserved.
International Conference on Advanced Materials, Manufacturing, Management and Thermal Sciences (AMMMT) -- SEP 23-24, 2016 -- Siddaganga Inst Technol, Tumkur, INDIA
Keywords: Shape memory alloys; Shape memory characteristics; Transformation temperatures; Microstructural analysis; Phase analysis